Suitability in compounding sterile preparations: An observational study in a referral hospital - Erza Genatrika; Ika Puspitasari; Susi Ari Kristina; Teuku Nanda Saifullah Sulaiman (GarVal Editorial Ltda., 2022)
Context: Compounding sterile preparations in hospitals requires special attention because the process is more complex. Errors that occur when compounding sterile preparations can cause contamination of the prepared preparations. Aims: To evaluate the compounding of sterile preparations in a referral hospital. Methods: This research was conducted by observing nine critical aspects in the compounding of sterile preparations. The research instrument used was a checklist, as regulated in USP <797> Guidelines and Basic Guidelines for Dispensing Sterile Preparations. After that, the most mixed preparations were tested for sterility using a fluid thioglycollate medium and soybean casein digest medium. Results: Of the 36 compounding sterile preparations, discrepancies were found in the aspects of compounding personnel (100%), building (100%), equipment (100%), aseptic procedures (100%), packaging (0%), labels (100%), storage (2.78%), distribution (2.78%) and quality assurance (100%). Furthermore, sterile preparations prepared in the cleanroom in this referral hospital indicate the occurrence of microbial contamination. Conclusions: Most of the critical aspects in compounding sterile preparations at this referral hospital have not met the recommendations of the USP <797> Guidelines and the Basic Guidelines for the Dispensing of Sterile Preparations, except for the packaging aspect. Improvements in several critical aspects need to be made to ensure the quality of the prepared preparations from microbial contamination.